Avoiding Health Information - Barbour, Joshua B.; Rintamaki, Lance S.; Ramsey, Jason A.; Brashers, Dale E. (Journal of health communication, 2012)
This study investigated why and how individuals avoid health information to support the development of models of uncertainty and information management and offer insights for those dealing with the information and uncertainty inherent to health and illness. Participants from student (n = 507) and community (n = 418) samples reported that they avoided health information to (a) maintain hope or deniability, (b) resist overexposure, (c) accept limits of action, (d) manage flawed information, (e) maintain boundaries, and (f) continue with life/activities. They also reported strategies for avoiding information, including removing or ignoring stimuli (e.g., avoiding people who might provide health advice) and controlling conversations (e.g., withholding information, changing the subject). Results suggest a link between previous experience with serious illness and health information avoidance. Building on uncertainty management theory, this study demonstrated that health information avoidance is situational, relatively common, not necessarily unhealthy, and may be used to accomplish multiple communication goals.